(untitled) (Plant Tissue Culture and Biotechnology, 2008)
In five cultivated rice varieties e.g., Nonabokra, PNR 381, Taipei 309, Koshika and TKM 11 the response in the initiation of callus and its size varied greatly among varieties, salt concentrations (NaCl and Na2SO4) and their interaction. Better regeneration ability of Nonabokra, Koshika and TKM 11 was found to be correlated to small size callus with a high concentration of Na2SO4. The regeneration ability found here was dependent on variety/genotype, callus type and size, source of salt and their concentration. Regeneration ability enhanced three - tenfolds from Na2SO4 stressed callus compared to the control i.e. without Na2SO4. Vigorous rooting was also observed in the regenerated plants obtained from the calli induced in the medium containing Na2SO4. In NaCl supplemented medium, on the other hand, regeneration and rooting ability were poor. Key words: Rice varieties, Regeneration efficiency, Shoot regeneration DOI = 10.3329/ptcb.v16i1.1105 Plant Tissue Cult. & Biotech. 16(1): 45-52, 2006 (June)